Protective effects of wogonin in the treatment of central nervous system and degenerative diseases - Qingan Fu; Qingyun Yu; Hongdan Luo; Zhekang Liu; Xiaowei Ma; Huijian Wang; Zhijuan Cheng (Brain Research Bulletin)
Wogonin, an O-methylated flavonoid extracted from Scutellaria baicalensis, has demonstrated profound neuroprotective effects in a range of central nervous system (CNS) diseases. This review elucidates the pharmacological mechanisms underlying the protective effects of wogonin in CNS diseases, including ischemic stroke, hemorrhagic stroke, traumatic brain injury, epilepsy, anxiety, neurodegenerative diseases, and CNS infections. Wogonin modulates key signaling pathways, such as the MAPK, NF-κB, and ROS pathways, contributing to its anti-inflammatory, antioxidant, and antiapoptotic properties. In ischemic stroke models, wogonin reduces infarct size and enhances neurological outcomes by mitigating inflammation and oxidative stress. For patients with hemorrhagic stroke and traumatic brain injury, it accelerates hematoma regression, mitigates secondary brain damage, and promotes neurogenesis, making it an entirely new treatment option for patients with limited access to this type of therapy. Its anticonvulsant and anxiolytic effects are mediated through GABA-A receptor modulation. Moreover, wogonin shows promise in treating neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease by promoting autophagy and reducing neuroinflammation. Additionally, it exhibits antiviral properties, offering potential benefits against CNS infections. Despite extensive preclinical evidence, further clinical studies are warranted to confirm its efficacy and safety in humans. This review highlights the great therapeutic potential of wogonin in terms of CNS protection. However, despite the substantial preclinical evidence, further large-scale clinical studies are necessary. Future researchers need to further explore the long-term efficacy and safety of wogonin in clinical trials and translate it for early application in the clinical treatment of true CNS disorders.